A Comprehensive Analysis of External Debt, Investment, and Economic Growth Applied to OIC Member Countries - Rahimjon, Dilbarova Malika; Saleh, Husny Gibreel Musa; Andriamiandrisoa, Hoby Nasandratra (Universitas Bojonegoro, 2025)
The relationship between foreign debt, investment, and economic growth in nations that are members of the Organisation of Islamic Cooperation (OIC) is the main subject of this study. Using a panel data model, the goal is to examine the intricate dynamics and interdependencies that shape these nations' economic trajectories. The paper explores the potential and difficulties associated with foreign debt, investment, and economic growth in OIC member nations by looking at the theoretical foundations, empirical data, and statistical analysis. Regression analysis results show that external debt can affect investment and economic growth in both positive and negative ways. The study highlights how crucial it is to comprehend these links while taking into account the unique context of OIC member nations. All things considered, this study advances knowledge of international economics and offers guidance to decision-makers in the creation of sensible economic policies.